Valve‐in‐valve using an Edwards Sapien XT into a JenaValve in a patient with a low originating left coronary artery and a heavily calcified aorta. Issue 5 (13th August 2015) - Fujita, Buntaro; Scholtz, Smita; Ensminger, Stephan
Abstract : Coronary obstruction during transcatheter aortic valve implantation is a potentially life‐threatening complication. Most of the widely used transcatheter heart valves require a certain distance between the basal aortic annular plane and the origins of the coronary arteries. We report the case of a successful valve‐in‐valve procedure with an Edwards SAPIEN XT valve into a JenaValve as a bail‐out procedure in a patient with a low originating left coronary artery and a heavily calcified aorta. © 2015 Wiley Periodicals, Inc.